A Pathfinding Module for the Indoor Navigation System NaviSecure - Nazarczuk, Maciej; Niewiadomski, Artur (Studia Informatica. System and information technology, 2025)
NaviSecure is an indoor navigation system developed atUniversity of Siedlce. It utilizes a dedicated hierarchical building map and an infrastructure of Bluetooth Low Energy transmitters, as well as hazard detectors such as smoke, flood, and gas sensors. The system facilitates daily navigation and provides emergency assistance while addressing the needs of individuals with disabilities. In this paper we present the pathfinding module of the NaviSecure system, implemented on top of the Neo4j graph database. We introduce the basic concepts behind our approach, we discuss the system architecture and our custom approach to deal with special needs of the users. Finally, we show the results of our experimental evaluation of several graph algorithms, modified to meet NaviSecure’s specific requirements. The results confirm the efficiency of our approach.